Lexical inferencing in reading an English text: An introspective study - Kusiak-Pisowacka, Monika (Papers in Linguistics, 2023)
The aim of the paper is to present the results of a think-aloud study which investigated how Polish learners of EFL coped with unknown words in a written text. The following aspects of the inferencing process were explored: the strategies and types of knowledge sources used by the learners, the students’ individual patterns of strategy use, effectiveness in deducing word meanings and the reasons behind unsuccessful inferences. The results showed that the learners applied a range of cognitive and metacognitive strategies, with translation and paraphrasing as the most frequent ones, drawing on interlingual, intralingual and external sources of information. The students differed in their way of deducing the meanings of unknown words and the effectiveness of inferencing. The failures in deriving word meanings were attributed to poor skills of referring to global context and inability to follow semantic relations throughout the text.